An Introduction to Zooarchaeology - Gifford-Gonzalez, Diane (Springer, 2018)
In 1950, there were few, if any, zooarchaeologists. Today the number of zooarchaeologists in North America is growing toward equal proportions with those specializing in the more traditional fields of lithic and ceramic analysis (Zeder 1997). In earlier days, archaeologists sent the more complete bones and shells from their sites to zoologists or paleontologists who provided a list of species present. Lyman (2016a) reports that over 78% of North American reports on archaeofaunas published between 1900 and 1944 fell into this category. Faunal reports were usually in monographs’ appendices, listing taxonomic groups, sometimes with “rare,” “common,” or other quantitative estimates noted. In the 1960s and early 1970s several visionary paleontologists and zoologists began training young archaeologists in taxonomy and anatomical identification. Today, zooarchaeology is a self-reproducing field taught in many university departments of anthropology or archaeology. As archaeologists have literally taken faunal analysis into their own hands, they have debated how best to use animal remains to study everything from early hominin hunting or scavenging to animal production in ancient market economies.